2021
DOI: 10.1287/orsc.2021.1454
|View full text |Cite
|
Sign up to set email alerts
|

Anchored Differentiation: The Role of Temporal Distance in the Comparison and Evaluation of New Product Designs

Abstract: A new design can be compared with its contemporaries or older designs. In this study, we argue that the temporal distance between the new design and its comparison play an important role in understanding how a new design’s similarity with other designs contributes to its valuation. Construing the value of designs as a combination of their informational value and their expressive value, we propose the “anchored differentiation” hypothesis. Specifically, we argue that expressive value (which is enhanced by how m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…), product design is subject to the contrasting pressures of conformity and differentiation. Research has shown that the success of a product design depends not only on its typicality with other product designs to increase consumer familiarity but also on its differentiation from other designs to enhance its novelty and uniqueness (Askin & Mauskapf, 2017; Chan et al, 2021; Liu et al, 2017; Zhao et al, 2018). Moreover, product design differs from other firm‐level strategic dimensions because it faces a unique twofold challenge: first, it needs to manage the conformity–differentiation tension vis‐à‐vis other organizations' product design, and second, for organizations with multiple products, managing the same tension among these multiple products within the same organization is also necessary.…”
Section: Within‐ and Between‐organization Distinctiveness Of Product ...mentioning
confidence: 99%
See 1 more Smart Citation
“…), product design is subject to the contrasting pressures of conformity and differentiation. Research has shown that the success of a product design depends not only on its typicality with other product designs to increase consumer familiarity but also on its differentiation from other designs to enhance its novelty and uniqueness (Askin & Mauskapf, 2017; Chan et al, 2021; Liu et al, 2017; Zhao et al, 2018). Moreover, product design differs from other firm‐level strategic dimensions because it faces a unique twofold challenge: first, it needs to manage the conformity–differentiation tension vis‐à‐vis other organizations' product design, and second, for organizations with multiple products, managing the same tension among these multiple products within the same organization is also necessary.…”
Section: Within‐ and Between‐organization Distinctiveness Of Product ...mentioning
confidence: 99%
“…We propose that the extent to which distinctiveness benefits or hinders performance depends on the level at which distinctiveness is conceptualized. In particular, we focus on the distinctiveness of product design, or the visual form of a product, which is increasingly recognized as one of the most important drivers of a product's market performance (Bloch, 1995; Chan, Lee, & Jung, 2021; Chan, Mihm, & Sosa, 2018; Radford & Bloch, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…• Evolutionary capability (e.g. Bradley et al, 2012;Chan et al, 2021;Suarez and Lanzolla, 2005) • Interdependent association (e.g. Bogers et al, 2017; Table 2.…”
Section: • How Does Communal Dynamic Feed Back Into Open Innovation P...mentioning
confidence: 99%
“…Additionally, when it comes to the evolution of digital goods, individuals often find it difficult to assess when a product may evolve into something superior to its rivals (Bradley et al, 2012;Chan et al, 2021;Suarez and Lanzolla, 2005). Do there exist any factors that affect the evolvability of digital goods applied to innovation diffusion initiatives?…”
Section: Research Directions From the Cross-level Perspectivementioning
confidence: 99%
See 1 more Smart Citation